Grzegorz z Nyssy: czy Bóg stworzył starość? - Przyszychowska, Marta (Vox Patrum, 2011)
Old age, which we consider to be a normal or even a natural stage of human life, seems to us inseparably bound with human condition. However, for Gregory of Nyssa old age, like youth, sexual reproduction, passions or pain, was a consequence of the first sin rather than a characteristic feature of human nature, which was created by God at the beginning. In man’s beginnings God performed three important acts. In the first act He created human nature considered to be an entity, without separation into male or female. During the second stage of creation God – anticipating sin of the first man – created individual human beings with specific sex. The third act took place after the sin, when God gave people clothes made of animal skins, by which Gregory understands an animal aspect of human life, alien to human nature, and old age is an element of this aspect. Nevertheless, in our present condition clothes made of animal skins could be used for a good cause, so also old age could be a stage on the road to eternal life. Although God did not plan it for man, after the first sin it has become for us something normal and even natural.